Molecular events following gluten stimulation in coeliac disease - Bracken, Suzanne (Trinity College (Dublin, Ireland). Department of Immunology, 2006)
Coeliac disease is a common autoimmune disorder, caused by an intolerance to dietary gluten in genetically predisposed individuals. Despite the advances in understanding of the nature of the disease, it remains unknown how gluten peptides breach the epithelium to initiate the inflammatory cascade and why certain gluten peptides trigger different aspects of the immune response. Investigations into gluten peptides have been conducted since the 1950s with the main focus examining the properties of wheat. In recent years, oats have received much attention due to opposing reports on their effect in coeliac patients. Barley and rye, although excluded from the official Codex Alimentarius gluten- free diet since the 1970s, have a lack of scientific evidence regarding their damaging effects.
Keywords: Immunology, Ph.D.; Ph.D. Trinity College Dublin